Luminescent protein staining with Re(i) tetrazolato complexes. Issue 28 (28th June 2018) - Fiorini, Valentina; Bergamini, Linda; Monti, Nicola; Zacchini, Stefano; Plush, Sally E.; Massi, Massimiliano; Hochkoeppler, Alejandro; Stefan, Alessandra; Stagni, Stefano
Abstract : Re(i ) tricarbonyl diiimine complexes for the first time exploited as luminescent staining agents for SDS-PAGE. Abstract : Within the general framework of our past and current studies dealing with the investigation of the photophysical properties and the biological behavior of the family of tetrazolato and tetrazole Re(i ) complexes, we have endeavored to investigate their potential in the luminescent staining of proteins purified by acrylamide gel electrophoresis. With the aim to provide the first examples of luminescent Re(i ) complexes to be exploited for this specific purpose, we have designed and prepared four new Re(i )-based species with the general formula fac -[Re(CO) 3 (N^N)(Tph)] 2−/0, whereTph is the 5-(phenyl)tetrazolato anion andN^N is in turn represented by bathophenanthroline disulfonate (BPS ), bathocuproine disulfonate (BCS ) or by the SO3 − free bathocuproine (BC ). In this latter case, the neutral complex fac -[Re(CO)3 (BC)(Tph)] served as a model species for the characterization of the former disulfonate complexes. Its cationic analogue fac -[Re(CO)3 (BC)(Tph-Me)] + was also prepared by a straightforward methylation reaction. All complexes displayed bright phosphorescence in organic media and, relative to their water solubility, the dianionic species fac -[Re(CO)3 (BPS)(Tph)] 2− and fac -[Re(CO)3 (BCS)(Tph)] 2− were also highly emissive in aqueous solution. The sulfonate groups played a key role in promoting and significantly enhancing the luminescent staining performances of both the Re(i ) complexes fac -[Re(CO)3 (BPS)(Tph)] 2− and fac -[Re(CO)3 (BCS)(Tph)] 2− for proteins. Highlighting a response superior to that of Coomassie Blue and comparable to the one obtained by the well-known silver staining method, these dianionic Re(i )-complexes could efficiently detect up to 50 ng of pure Bovine Serum Albumin (BSA), as well as all proteins found in a Standard Protein Marker mix and from a total protein extract. A lower but still good response for luminescent protein staining was surprisingly obtained by employing the –SO3 − free neutral and cationic complexes fac -[Re(CO)3 (BC)(Tph)] and fac -[Re(CO)3 (BC)(Tph-Me)] +, respectively. These preliminary results open up new possibilities for the further widening of the use of Re(i )-based complexes as luminescent protein staining agents.